A systematic quantification of hemodynamic differences persisting after aortic coarctation repair - Jensen, Christopher; Ghorbannia, Arash; Urick, David; Hughes, G. Chad; Randles, Amanda (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAortic coarctation (CoA) comprises 6%–8% of all congenital heart diseases and is the second most common cardiovascular disease requiring neonatal surgical correction. However, patients remain at high risk for long-term complications, notably recoarctation.MethodsHemodynamic simulations were performed in a group of six patients following CoA repair, as compared to a group of age and sex-matched healthy controls. Progressive narrowing at the CoA repair site was modeled to simulate the recoarctation process. Key measurements included time-averaged wall shear stress (TAWSS) in the aortic arch and CoA repair site.ResultsRepaired aortas demonstrated significantly higher TAWSS compared to healthy aortas in the aortic arch (3.46 vs 1.24 Pa, p< 0.05) and CoA repair site (4.34 vs 1.56 Pa, p< 0.05). A pronounced nonlinear relationship between stenosis severity and TAWSS was observed suggesting that increasing stenosis corresponds to progressively abnormal shear stress.DiscussionThe persistent high TAWSS in CoA-repaired aortas may underlie the poor long-term outcomes observed in this population. The identified nonlinear relationship between stenosis severity and TAWSS magnitude suggests a potential positive feedback mechanism, where abnormal shear stress exacerbates pathologic remodeling in the repaired aorta, highlighting the potential role of hemodynamic simulations in the clinical management of CoA patients.